Optimizing the Quality of Learning Through the Role of Educational Administration - Hasrat A Aimang; Armin Haluti; Ma Cristina D Ravela (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to identify and analyze the role of educational administration in improving the quality of learning in Senior high schools in Luwuk City. The main focus is to understand how effective educational administration can support a better learning process and address existing challenges at the school level. Methodology: This study adopts a qualitative approach with a descriptive method. Data was collected through semi-structured interviews with principals, teachers, and administrative staff from several high schools in Luwuk City. Data analysis was conducted using thematic analysis to identify key themes related to educational administration management and learning quality in schools. Main Findings: The results of the study show that good education administration can improve the quality of learning by managing time, budget, and resources more efficiently. However, the main challenges found are the lack of managerial training for administrative staff as well as budget constraints that affect the quality of available educational facilities and resources. Schools with more organized administration showed better management of learning activities and higher student participation. Novelty/Originality of this study: This research contributes significantly to education management by highlighting the importance of educational administration in enhancing learning quality, especially in areas with limited resources and managerial capacity. Additionally, it proposes a more systematic approach to educational administration management that can improve learning quality in Luwuk City High Schools, a local context seldom discussed in educational literature.